(untitled) (Swiss Medical Weekly, 2013)
Chronic synovial inflammation in rheumatoid arthritis (RA) leads to progressive damage to articular cartilage and bone, ultimately resulting in disability. Therefore, control of the articular inflammation is of great importance to prevent joint damage. A variety of disease-modifying antirheumatic drugs (DMARDs) are available for RA patients. Conventional synthetic DMARDs, and in particular biological DMARDs, have been shown to effectively inhibit joint destruction in RA. Longitudinal assessments of radiographic changes in patients with RA in clinical trials and in large patient registries have clearly shown that delays in the initiation of DMARD therapy results in significantly increased progression of joint damage. Patients started early on DMARDs had significantly lower radiographic damage progression than patients initiating DMARD treatment later. These effects were maintained for several years, suggesting that early in the development of RA a therapeutic window of opportunity exists in which DMARD therapy decisively influences the long-term prognosis. Therefore, to improve the clinical outcome of RA, our efforts should be directed towards diagnosing RA earlier and introducing DMARD therapy immediately after the diagnosis has been made. Key words: biologic; bone erosion; DMARD; joint damage; radiographic progression; rheumatoid arthritis; SCQM; window of opportunity